Ultrasound assessment of endothelial dysfunction in Egyptian migraine patients - Haidy Elshebawy; Ebtesam Mohamed Fahmy; Mona Abd El Fattah Nada; Nouran Alaa Abd El Hamid; Sarah Heneidy (SpringerOpen, 2024)
Abstract Background It becomes clearer that migraine is associated with vascular risks; however, preclinical vascular involvement is not sufficiently addressed. Evidences point that migraine attacks affect vascular endothelium. The aim of this study was to investigate endothelial dysfunction in migraineurs through assessment of carotid intima-media thickness (CIMT) and flow-mediated dilatation (FMD) of the brachial artery and their correlation with clinical characteristics of migraine, headache severity, and brain magnetic resonance imaging (MRI) findings. Results A statistically significant difference was found between migraineurs and controls where carotid IMT was significantly higher and FMD of the brachial artery was significantly lower in migraineurs compared to controls. Carotid IMT was significantly higher and FMD was significantly lower in chronic migraine compared to episodic migraine patients. Mean IMT values were significantly higher in patients receiving ergots and in patients with subcortical white matter lesions in brain MRI. Mean FMD values were significantly lower in patients receiving ergots. There was a significant negative correlation between FMD and carotid IMT, age of the patients, disease duration, duration of headache attacks, headache frequency, and migraine disability assessment questionnaire (MIDAS) score. There were significant positive correlations between carotid IMT and age of patients, disease duration, headache frequency, MIDAS score, and number of MRI white matter lesions. For diagnosing endothelial dysfunction in migraineurs, the sensitivity and specificity of IMT were 72.5 and 70%, respectively, with a cut-off value of 0.575 mm and that of FMD were 82.5 and 90%, respectively, with a cut-off value of 20.55%. Conclusion Migraine coincides with endothelial dysfunction which promotes atherogenesis and increased risk of cerebral ischemia. FMD could be used as a potential biomarker for endothelial dysfunction in migraine. The affection of IMT and FMD is more in patients receiving ergots which may influence the selection of treatment in migraineurs in the future.